Simulation of palm oil and methanol mixing in stirred tank by implement a normal and fractal baffles - Asmayou, Ali. H. (2014)
Numerical analysis of mixing and dissolution processes is becoming great significant for achieving a process of consideration and optimizing the production. Owing to the rising costs and deficiency of raw materials, “palm oil” processes are presently employed together with standard experimental analysis. Numerical simulations have confirmed to be a valuable instrument for understanding and enhancing industrial mixing problems. However, such simulations are still in the research phase. Even though Computational Fluid Dynamics (CFD) is a powerful and validated method, however, for more complicated applications (e.g., industrial mixing), more work is still required to gain reliable results quickly enough. In this project concentrated on the simulation of two type of tank to compare between normal baffle and fractal baffle in mixing tank to get which one is the best of homogenizing. Approximations were made with respect to improving batch sizes, tank geometry, impeller type, baffle type, and placement and process variables, such as the impeller agitation speed. In addition, the feeding position of the methanol. Finally, a quantitative comparison of different stirring systems and scale-up studies was set.